Pengaruh Struktur Modal Dan Kinerja Keuangan Terhadap Manajemen Laba Pada Perusahaan Sektor Consumer Non-Cyclicals (CNC) Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2022 - Ramdona, Sinta Sri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to analyze the effect of capital structure and financial performance on earnings management practices in consumer non-cyclicals (CNC) sector companies listed on the Indonesia Stock Exchange. Using quantitative methods, this study involved 118 samples of annual report data for the 2021-2022 period. The results of the analysis show that capital structure has a significant negative effect on earnings management. In contrast, financial performance has a significant positive effect on earnings management. Although both variables have a significant effect simultaneously, the coefficient of determination shows that most of the variation in earnings management is influenced by other factors, such as regulation and corporate governance.